2010
DOI: 10.1053/j.ajkd.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Early Urinary Markers of Diabetic Kidney Disease: A Nested Case-Control Study From the Diabetes Control and Complications Trial (DCCT)

Abstract: Background-Urinary markers were tested as predictors of macroalbuminuria or microalbuminuria in type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 42 publications
2
71
0
1
Order By: Relevance
“…reported that urinary NAG predicted the occurrence of albuminuria in patients with diabetes mellitus (36). We are, to our knowledge, the first to investigate how a panel of markers associated with damage to different parts of the nephron relates to progression of albuminuria.…”
Section: Discussionmentioning
confidence: 87%
“…reported that urinary NAG predicted the occurrence of albuminuria in patients with diabetes mellitus (36). We are, to our knowledge, the first to investigate how a panel of markers associated with damage to different parts of the nephron relates to progression of albuminuria.…”
Section: Discussionmentioning
confidence: 87%
“…[32][33][34][35] In the present study, increased NAG ratio was found in the same risk groups, which is in line with the existing literature. 20,22,[36][37][38][39][40][41] The associations with the end points may therefore in part be explained by the more adverse risk profile among individuals with increased NAG ratio. However, because the associations were independent from the traditional cardiovascular risk factors, ACR, and hsCRP, explanations other than NAG ratio solely reflecting an adverse risk profile and inflammation should be sought.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between urinary NAG and end-organ damage has been assessed mainly in cross-sectional studies of diabetic patients [16][17][18][19] and in hypertension. 20 Prospective studies of the association between urinary NAG excretion and future development of disease are scarce and have only been carried out in patients with diabetes 21,22 and chronic heart failure. 23 To our knowledge, the role of urinary NAG as a risk factor for myocardial infarction, ischemic stroke, and all-cause mortality has never been investigated, either in patient groups or in the general population.…”
mentioning
confidence: 99%
“…On the other hand, a small study in patients with T1D suggested that low urinary levels of KIM-1 and Nacetyl-β-D-glucosaminidase (NAG) are independently associated with regression from moderate albuminuria to normoalbuminuria [87]. A nested case-control study in DCCT also reported that elevated urinary NAG levels independently predict the development of moderate and severe albuminuria [88].…”
Section: Novel Markers For the Early Diagnosis Of Diabetic Nephropathymentioning
confidence: 99%